ANALISIS PENGENDALIAN KUALITAS STATISTIK INJECTION MOULDING PRODUK CUP PLASTIK Ø 80 mm x 70 mm - Etik Puspitasari (INFO-TEKNIK, 2016)
Plastic is used to make a wide range of products for example to tableware such as plates, cups, spoons and various other equipment. The advantages of this plastic material is resistant to corrosion, its density is low enough so that it can float, process of formation of a plastic material into a product one of them with a system of injection molding plastic products, namely printing process that is generally used for the type of thermoplastic plastics material.The research was conducted on the product plastic cup Ø 80 mm x 70 mm with injection molding systems. using a quality control method that aims to identify and analyze the types of product defects and factors are a major cause of disability so as to minimize the number of defective products and can improve the quality of products produced. From the results of Pareto diagram didapatkan.jenis major flaw for an immediate improvement in product plastic cup Ø 80 mm x 70 mm with injection molding system is defective flashing with a frequency number of failed products by 43% and the probability of failure of 0.43.Based on the fishbone diagram which constitutes the main factor defective product plastic cup Ø 80 mm x 70 mm is flashing where the cause is due to the injection pressure is too high. And remedial efforts to prevent defective products plastic cup Ø 80 mm x 70 mm with a system of injection molding is less injection pressure to minimize or eliminate the flashing because of the high pressure caused the material get into places that are not fitting in the mold.